Lithium ion battery and application thereof
By using additives such as fluorovinyl carbonate in lithium-ion batteries to form high-efficiency SEI, the thickness increase and diving of low-liquid liquid-retaining coefficient batteries during the circulation process of the silicon negative electrode system are solved, and the circulation performance and safety of the battery are improved.
Patent Information
- Application Number
- CN202411267568.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-11
- Publication Date
- 2025-01-10
- Estimated Expiration
- 2044-09-11
AI Technical Summary
The silicon negative electrode system in lithium-ion batteries has problems such as thickness growth and rapid circulation attenuation during the circulation process, and the subsistence-liquid liquid-receiving battery is prone to diving in the later stages of long cycles, resulting in safety hazards.
Using an electrolyte containing fluorovinyl carbonate, difluorovinyl carbonate, adipiconet and 1,3,6-hexanetrinitrile, these additives form efficient SEI in the electrolyte, and optimize the SEI Structure and performance, inhibit the volume change of silicon negative electrode and the growth of cell thickness, and adjust the additive ratio in the electrolyte to balance the function and stability of SEI.
It effectively suppresses the thickness growth and capacity attenuation of lithium-ion batteries during the cycle process, extends the cycle life of the battery, and avoids the problem of diving in the later stages of long cycles, improving the safety of the battery.
Smart Images

Figure BDA0005037596970000101 
Figure BDA0005037596970000111 
Figure BDA0005037596970000121
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of lithium ion battery processing, and in particular relates to a lithium ion battery and application thereof. Background Art
[0002] In order to increase the volume energy density of lithium-ion batteries, major lithium-ion battery manufacturers have begun to use a mixture of graphite and silicon as negative electrode active materials on a large scale. Graphite itself has relatively stable performance, mature production technology, and low cost, but its gram capacity is low, with a theoretical gram capacity of only 372mAh / g, which limits the increase in the gram capacity of the negative electrode. Silicon has a maximum theoretical gram capacity of 4200mAh / g, which is much higher than graphite, and is conducive to increasing the gram capacity of the negative electrode, thereby increasing the energy density of lithium-ion batteries. However, the silicon material itself will undergo a huge volume change during the charging process, causing the binder to fail, the distance between the negative electrode materials to increase, and the active material to separate from the current collector, causing the lithium-ion battery to have an irreversible thickness increase during the cycle process. At the same time, the huge volume expansion of the silicon negative electrode will cause the SEI on its surface to be in an unstable state. The SEI is in a repeated process of damage and repair for a long time, which makes the active Li inside the battery + Continuous consumption causes capacity decay. Therefore, improving cycle performance and inhibiting thickness growth during the cycle are the biggest challenges facing silicon negative electrode lithium-ion batteries.
[0003] By reducing the liquid retention coefficient of lithium-ion batteries, the amount of electrolyte floating inside the lithium battery can be effectively reduced, the effect of the floating liquid on the adhesion of the diaphragm can be reduced, and lithium precipitation and thickness growth during the cycle can be inhibited. However, after the liquid retention coefficient is reduced, the battery cell is prone to cycle diving in the later stage of the cycle, so generally low thickness growth and long cycle cannot be taken into account at the same time.
[0004] Therefore, there is an urgent need to develop an electrolyte that is suitable for high-voltage lithium cobalt oxide-graphite / silicon mixed negative electrode systems, and can inhibit the growth of battery thickness during the cycle process and inhibit the diving problem of low-retention coefficient batteries in the late stage of long cycles to avoid safety hazards. Summary of the invention
[0005] The following is a summary of the subject matter described in detail herein. This summary is not intended to limit the scope of the claims.
[0006] The present invention aims to at least solve the technical problems of the silicon negative electrode system in the above-mentioned prior art, such as the rapid thickness growth and cycle attenuation during the cycle, and the low liquid retention coefficient battery diving in the late stage of long cycle. To this end, the present invention proposes a lithium ion battery and its application. The electrolyte used in the present invention is particularly suitable for a high-voltage lithium cobalt oxide-graphite / silicon mixed negative electrode system, which can inhibit the growth of the battery thickness during the cycle, and inhibit the diving problem of the low liquid retention coefficient battery in the late stage of long cycle, avoiding safety hazards.
[0007] To achieve the above object, the present invention adopts the following technical solutions:
[0008] The present invention provides a lithium ion battery, comprising:
[0009] Electrolyte; the electrolyte comprises a lithium salt, a solvent and an additive, wherein the additive comprises fluoroethylene carbonate, difluoroethylene carbonate, adiponitrile and 1,3,6-hexanetrinitrile;
[0010] Positive electrode;
[0011] A negative electrode plate; the active material of the negative electrode plate comprises silicon material and graphite; and,
[0012] Isolation film;
[0013] The lithium ion battery satisfies 8≤8*(α*β / 2+σ 2 )+30*ln(σ*u / 5+γ 2 / 25)+10 / min(σ*u*γ*v, σu / v, 100*w*α / β)≤130, wherein α is the mass percentage of the fluoroethylene carbonate in the electrolyte, β is the mass percentage of the difluoroethylene carbonate in the electrolyte, γ is the mass percentage of the adiponitrile in the electrolyte, w is the mass percentage of the 1,3,6-hexanetrinitrile in the electrolyte, σg / Ah is the liquid retention coefficient of the lithium ion battery, uμm is the median particle size of the silicon material, and v is the mass percentage of the silicon material in the active substance.
[0014] The present invention introduces a new type of fluorocarbonate compound: difluoroethylene carbonate (DFEC) into the electrolyte system. DFEC has an efficient film-forming effect. It can preferentially form a film on the negative electrode during the formation process to form a SEI with a high LiF content, increase the LiF / Li2O ratio in the SEI and the ionic conductivity of the SEI, improve the charge and discharge performance, and help solve the problems of rapid thickness growth and cycle attenuation during the cycle of the silicon negative electrode system, as well as the problem of low liquid retention coefficient battery diving in the late stage of long cycle. In addition, fluoroethylene carbonate (FEC) as a negative electrode film-forming additive can reduce impedance and improve cycle performance, and adiponitrile (AND) and 1,3,6-hexane trinitrile (HTCN) can improve high-temperature storage and cycle performance. The above additives work together with DFEC to synergistically improve the cycle performance of the battery.
[0015] In addition, the present invention also constructs a relationship between different parameters. When the above conditions are met, DFEC and Li + The easiest to combine, the energy barrier is minimized, DFEC can preferentially combine with Li +Combined with a single electron reduction reaction, a higher Young's modulus LiF is generated on the surface of silicon particles, thereby increasing the LiF / Li2O ratio in SEI, making the SEI film more able to withstand the huge volume change of the silicon negative electrode during charging and discharging, thereby extending the cycle life of the lithium-ion battery. When the value of the above relationship is less than 8, FEC and Li + The easiest to combine, the energy barrier is reduced to the lowest, and a two-electron reduction reaction occurs to form organic components such as polymers. At the same time, EC is more easily reduced at the negative electrode to produce organic components such as Li2O, LiCO3 and alkyl carbonates, which reduces the LiF / Li2O ratio in the SEI film. At the same time, the proportion of organic components in the SEI also increases, making the stability of the SEI film worse, resulting in deterioration of the cycle performance. On the contrary, when the value of the above relationship is greater than 130, FEC and Li + The two-electron reduction reaction is more likely to occur, the content of organic components in SEI is further increased, the SEI stability is further reduced, the cycle performance is deteriorated, and the high-temperature storage performance is significantly affected, resulting in high-temperature storage gas production and capacity attenuation.
[0016] In general, the present invention constructs a relationship between different parameters and determines an electrolyte suitable for a graphite / silicon material mixed negative electrode system. The electrolyte suppresses the growth of battery thickness during the cycle process and suppresses the battery diving problem in the late stage of a long cycle, thereby avoiding safety hazards.
[0017] In some embodiments of the present invention, the mass percentage of the fluoroethylene carbonate in the electrolyte is 1% to 20%.
[0018] When the FEC content is too low, it cannot effectively form a film on the negative electrode surface and cannot protect the negative electrode active material. Side reactions on the negative electrode surface are more likely to occur, affecting the cycle performance.
[0019] In some embodiments of the present invention, the mass percentage of the bisfluoroethylene carbonate in the electrolyte is 0.4% to 10%, preferably 3% to 10%.
[0020] DFEC is a key substance to inhibit the expansion of silicon negative electrode. Under the premise of not deteriorating the charging, an appropriate amount of DFEC can increase the LiF content in SEI and reduce the growth of battery cell thickness during the cycle.
[0021] In some embodiments of the present invention, the mass percentage of adiponitrile in the electrolyte is 0.3% to 1.5%, for example, 0.5% to 1.5%, 0.5% to 1.2%, or 0.8% to 1.2%.
[0022] When the ADN content is too low, there is no obvious improvement effect, while when the content is too high, it will lead to significant deterioration of normal temperature cycle and low temperature discharge performance.
[0023] In some embodiments of the present invention, the mass percentage of the 1,3,6-hexanetrinitrile in the electrolyte is 0.3% to 3%, for example, 0.5% to 2.5%, 1% to 2.5%, or 1% to 2%.
[0024] When the HTCN content is too low, there is no obvious improvement effect, while when the content is too high, it will lead to significant deterioration of normal temperature cycle and low temperature discharge performance.
[0025] In some embodiments of the present invention, the lithium salt is selected from at least one of lithium hexafluorophosphate (LiPF6), lithium difluorophosphate (LiDFP), lithium difluorobisoxalate phosphate (LiODFP), lithium tetrafluorooxalate phosphate (LiOTFP), lithium bisoxalatoborate (LiBOB), lithium difluorooxalatoborate (LiODFB), lithium tetrafluoroborate (LiBF4), bistrifluoromethanesulfonyl imide lithium salt (LiTFSI) and bis(trifluorosulfonyl) imide lithium salt (LiFSI).
[0026] In some embodiments of the present invention, the mass percentage of the lithium salt in the electrolyte is 8% to 25.0%, for example, 8% to 20.0%, 8% to 15.0%, 10% to 20.0%, 10% to 15.0%, 12% to 20.0%, 12% to 15.0%, or about 14%.
[0027] In some embodiments of the present invention, the solvent includes at least one of a non-fluorinated carbonate solvent, a carboxylate solvent, an ether solvent, and a C2-C5 nitrile solvent.
[0028] Wherein, the non-fluorinated carbonate solvent is selected from at least one of ethylene carbonate (EC), propylene carbonate (PC), dimethyl carbonate (DMC), diethyl carbonate (DEC), dipropyl carbonate (DPC), ethyl methyl carbonate (EMC), methyl propyl carbonate (PMC), and ethyl propyl carbonate (PEC); the carboxylic acid ester solvent is selected from at least one of methyl acetate (MA), ethyl acetate (EA), propyl acetate (EP), butyl acetate, methyl propionate, ethyl propionate, propyl propionate (PP), methyl butyrate, and ethyl butyrate; the ether solvent is selected from at least one of tetrahydrofuran, 1,3-dioxolane, ethyl ether, ethylene glycol dimethyl ether, diethylene glycol dimethyl ether, triethylene glycol dimethyl ether, and tetraethylene glycol dimethyl ether; the C2-C5 nitrile solvent is selected from at least one of acetonitrile, glutaronitrile, and malononitrile.
[0029] In some preferred embodiments of the present invention, the solvent includes a non-fluorinated carbonate solvent and a carboxylate solvent.
[0030] In some preferred embodiments of the present invention, the solvent includes ethylene carbonate, propylene carbonate, diethyl carbonate and propyl propionate; more preferably, the mass ratio of ethylene carbonate, propylene carbonate, diethyl carbonate and propyl propionate is 10-30:5-15:30-50:20-40.
[0031] In some embodiments of the present invention, the positive electrode sheet includes an aluminum foil current collector and a positive electrode membrane.
[0032] In some embodiments of the present invention, the positive electrode membrane includes a positive electrode active material, lithium cobalt oxide (LiCoO2); further, it also includes a conductive agent and a binder; wherein the weight ratio of LiCoO2, conductive agent, and binder is 98.5:0.5:1.
[0033] In some preferred embodiments of the present invention, the conductive agent is selected from at least one of Super-P, acetylene black (AB), Ketjen black (KB), and carbon nanotubes (CNT); more preferably, the conductive agent is Super-P.
[0034] In some preferred embodiments of the present invention, the binder is selected from at least one of polyvinylidene fluoride (PVDF), polyacrylic acid (PAA), and polytetrafluoroethylene (PTFE); more preferably, the binder is PVDF.
[0035] In some embodiments of the present invention, the silicon material is selected from at least one of silicon, silicon oxide, silicon monoxide, and silicon carbide.
[0036] In some embodiments of the present invention, the weight proportion of the silicon material in the active material is 3% to 20%, for example, 5% to 20%, 10% to 20%, or 15% to 20%.
[0037] If the proportion of silicon material in the active material is too low, the energy density of the lithium-ion battery cannot be effectively improved; if the proportion is too high, the side reactions on the negative electrode side will increase seriously, resulting in serious degradation of the cycle performance.
[0038] In some embodiments of the present invention, the median particle size of the silicon material is 2.3 to 7 μm, for example, 3 to 7 μm, 4 to 7 μm, or 4.5 to 7 μm.
[0039] If the particle size of the silicon material is too large, there will be fewer side reactions on the particle surface, but the capacity of the battery will gradually decrease; conversely, if the particle size of the silicon material is too small, the volume effect of the silicon particles during the charge and discharge process will be weakened, but the side reactions on the surface of the silicon particles will gradually intensify, causing the cycle performance to deteriorate; therefore, the particle size needs to be within an appropriate range to balance various performance factors.
[0040] In some embodiments of the present invention, the negative electrode plate further includes a copper foil current collector.
[0041] In some embodiments of the present invention, the negative electrode plate further includes a conductive agent, a thickener and a binder; wherein the weight ratio of the negative electrode active material, the conductive agent, the thickener and the binder is 97:0.8:1.2:1.
[0042] In some preferred embodiments of the present invention, the conductive agent is selected from at least one of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, and carbon nanofibers; more preferably, the conductive agent is a carbon nanotube.
[0043] In some preferred embodiments of the present invention, the thickener may be sodium carboxymethyl cellulose (CMC-Na).
[0044] In some preferred embodiments of the present invention, the binder can be selected from at least one of styrene-butadiene rubber (SBR), polyacrylic acid (PAA), sodium polyacrylate (PAAS), polyacrylamide (PAM), polyvinyl alcohol (PVA), sodium alginate (SA), polymethacrylic acid (PMAA) or carboxymethyl chitosan (CMCS); more preferably, the binder is PAA.
[0045] In some embodiments of the present invention, the injection coefficient of the lithium-ion battery is 1 to 2 g / Ah.
[0046] In some embodiments of the present invention, the liquid retention coefficient of the lithium ion battery is 1.0 to 1.5 g / Ah.
[0047] The range of the liquid retention coefficient in the present invention is relatively low, which can effectively inhibit the lithium deposition phenomenon of the battery cell during the cycle process and improve the cycle performance.
[0048] The present invention also provides an electronic device, comprising the above-mentioned lithium-ion battery.
[0049] The lithium-ion battery according to the embodiment of the present invention has at least the following beneficial effects:
[0050] The present invention introduces the key additive DFEC and utilizes its low reduction potential to form a film at the negative electrode in preference to FEC. The induced SEI has a higher LiF content than FEC, which helps to improve the stability of the SEI, reduce the rupture of the SEI film during the charge and discharge process, and improve the cycle performance of the lithium ion battery.
[0051] The relationship between the four additives DFEC, FEC, ADN, and HTCN and the silicon materials and battery cell parameters is constructed. By adjusting the ratio of the two key components LiF and Li2O in SEI, a balance is achieved between the film-forming performance and the SEI function. At the same time, the cycle diving of the battery cell in the low liquid retention state is suppressed to avoid safety risks of electronic equipment in the later stages of the cycle.
[0052] Terms and Definitions:
[0053] If not otherwise specified, the "filling coefficient" in the present invention refers to the ratio of the amount of electrolyte filled in the battery to the designed discharge capacity of the battery, measured in g / Ah.
[0054] If not otherwise specified, the "liquid retention coefficient" in the present invention refers to the ratio of the amount of remaining electrolyte in the battery cell after double sealing to the designed discharge capacity of the battery, and the unit is g / Ah.
[0055] Unless otherwise specified, "about" in the present invention means that the allowable error is within ±5%. DETAILED DESCRIPTION
[0056] The following will be combined with the embodiments to clearly and completely describe the concept of the present invention and the technical effects produced, so as to fully understand the purpose, characteristics and effects of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, other embodiments obtained by those skilled in the art without creative work are all within the scope of protection of the present invention.
[0057] Example
[0058] In the present invention, unless otherwise specified, all equipment and raw materials can be purchased from the market or are commonly used in the industry. The methods in the following embodiments, unless otherwise specified, are conventional methods in the art.
[0059] EC: ethylene carbonate;
[0060] PC: propylene carbonate;
[0061] DEC: diethyl carbonate;
[0062] PP: Propyl propionate;
[0063] LiPF6: lithium hexafluorophosphate;
[0064] FEC: fluoroethylene carbonate;
[0065] DFEC: bis(fluoroethylene carbonate);
[0066] ADN: adiponitrile, dinitriles;
[0067] HTCN: 1,3,6-hexanetrinitrile, ternary nitrile;
[0068] The main active material of the positive electrode, LiCoO2, was purchased from Xiamen Tungsten New Energy;
[0069] The diaphragm was purchased from Shenzhen Xingyuan;
[0070] The active materials graphite and silicon of the negative electrode were purchased from Shenzhen Bettery.
[0071] Example 1
[0072] This embodiment provides a lithium-ion battery, including a positive electrode sheet, a negative electrode sheet, a separator and an electrolyte, wherein the separator is disposed between the positive electrode sheet and the negative electrode sheet. The lithium-ion battery is assembled in the following manner:
[0073] 1.1 Preparation of electrolyte
[0074] The components in the electrolyte are shown in Table 1. In a glove box filled with argon, EC, PC, DEC, and PP were mixed in a mass ratio of EC: PC: DEC: PP = 20: 10: 40: 30, and then 14 wt% of lithium hexafluorophosphate (LiPF6) based on the total weight of the electrolyte was slowly added to the mixed solution, and finally 12 wt% of FEC, 3 wt% of additive DFEC, 1% of ADN, and 1.5% of HTCN based on the total weight of the electrolyte were added, and the lithium ion battery electrolyte was obtained after stirring evenly.
[0075] 1.2 Preparation of positive electrode
[0076] The cathode membrane includes the cathode active material lithium cobalt oxide LiCoO2, the conductive agent Super P, and the binder polyvinylidene fluoride PVDF. After mixing the materials in a weight ratio of LiCoO2:Super P:PVDF=98.5:0.5:1, adding them into N-methylpyrrolidone (NMP), mixing them evenly to prepare the positive electrode slurry of lithium-ion battery; coating the positive electrode slurry on the current collector aluminum foil, drying it at 85°C and cold pressing it, then trimming and striping it, drying it at 85°C under vacuum for 4h, welding the pole ears, and preparing the positive electrode sheet of lithium-ion battery.
[0077] 1.3 Preparation of negative electrode
[0078] The anode membrane includes graphite and silicon oxide, anode active materials, carbon nanotubes (CNT), a conductive agent, sodium carboxymethyl cellulose (CMC), and a binder, wherein the median particle size of silicon oxide material is u=4.8 μm. Graphite and silicon oxide are mixed in a weight ratio of 85:15 as negative electrode active materials, and each material is mixed in a weight ratio of negative electrode active material: CNT: CMC: PAA=97:0.8:1.2:1, and deionized water is added to mix uniformly to prepare a negative electrode slurry; the negative electrode slurry is coated on the current collector copper foil, dried at 85°C, cold pressed, trimmed and striped, and dried at 85°C under vacuum for 12 hours, and the tabs are welded to obtain a negative electrode sheet for a lithium-ion battery.
[0079] 1.4 Preparation of Lithium-ion Soft-Pack Batteries
[0080] The prepared positive electrode sheet (main active material LiCoO2), diaphragm, and negative electrode sheet (active material graphite and silicon) are stacked in order, with the diaphragm in the middle of the positive and negative electrode sheets, and wound to obtain a bare battery cell; the battery cell design capacity is 5.0Ah, and the voltage range is 3.0-4.55V. The bare battery cell is packaged in an aluminum-plastic film outer package, and then the battery cell is placed in an 85℃ vacuum oven for 48h. The electrolyte is injected into the dried battery with a liquid injection coefficient of 1.5g / Ah, and the battery is packaged, left to stand, formed, shaped, and divided, and then sealed again, with a liquid retention coefficient of 1.1g / Ah, to complete the preparation of lithium-ion soft-pack batteries.
[0081] Embodiment 2-9
[0082] Examples 2-9 each provide a lithium-ion battery, which is carried out with reference to Example 1, except that the composition ratios of the components of the electrolyte are different, as shown in Table 1.
[0083] Example 10
[0084] This embodiment provides a lithium ion battery, which is carried out with reference to the process in Embodiment 1, except that in "1.4 Preparation of lithium ion soft-pack battery", the liquid retention coefficient during the second sealing is σ=1.3 g / Ah.
[0085] Embodiment 11
[0086] This embodiment provides a lithium ion battery, which is carried out with reference to the process of Embodiment 1, except that the median particle size u of the silicon dioxide material in "1.3 Preparation of Negative Electrode Plate" is 6.5 μm.
[0087] Example 12
[0088] This embodiment provides a lithium-ion battery, which is carried out with reference to the procedure of Embodiment 1, except that in "1.3 Preparation of Negative Electrode Plate", the silicon negative electrode material accounts for v=20% of the total amount of negative electrode active material, that is, graphite and silicon dioxide are mixed in a weight ratio of 80:20 as the negative electrode active material.
[0089] Comparative Examples 1-4
[0090] Comparative Examples 1-4 each provide a lithium ion battery, which is carried out with reference to Example 1, except that the composition ratios of the components of the electrolyte are different, as shown in Table 1.
[0091] Comparative Example 5
[0092] This comparative example provides a lithium-ion battery, which is carried out with reference to Example 1, except that in "1.4 Preparation of lithium-ion soft-pack battery", the liquid retention coefficient during the second sealing is σ=1.9 g / Ah.
[0093] Comparative Example 6
[0094] This comparative example provides a lithium ion battery, which is carried out with reference to Example 1, except that the median particle size u of the silicon dioxide material in "1.3 Preparation of negative electrode sheet" is 8 μm.
[0095] Comparative Example 7
[0096] This comparative example provides a lithium-ion battery, which is carried out with reference to Example 1, except that in "1.3 Preparation of Negative Electrode Plate", the silicon negative electrode material accounts for v=30% of the total amount of negative electrode active material, that is, graphite and silicon dioxide are mixed in a weight ratio of 70:30 as the negative electrode active material.
[0097] Comparative Examples 8-12
[0098] Comparative Examples 8-12 each provide a lithium ion battery, which is carried out with reference to Example 1, except that the composition ratios of the components of the electrolyte are different, as shown in Table 1.
[0099] Comparative Example 13
[0100] Comparative Example 13 provides a lithium-ion battery, which is carried out with reference to Example 1, except that: the composition ratio of each component of the electrolyte is different, as shown in Table 1; in addition, in Comparative Example 13, the liquid retention coefficient σ during the second seal in "1.4 Preparation of lithium-ion soft-pack batteries" is 1.3 g / Ah, the median particle size u of the silicon oxide material in "1.3 Preparation of negative electrode sheets" is 7 μm, and the silicon negative electrode material in "1.3 Preparation of negative electrode sheets" accounts for v=20% of the total amount of negative electrode active material, and the rest is the same as in Example 1.
[0101] Table 1 Composition ratio of each component of the electrolyte of Examples 1-12 and Comparative Examples 1-13
[0102]
[0103]
[0104]
[0105] Test Case
[0106] Relevant performance tests were performed on the lithium-ion batteries prepared in Examples 1-12 and Comparative Examples 1-13.
[0107] (1) Normal temperature cycle performance test:
[0108] In a 25°C environment, the divided battery is charged to 4.55V at 0.7C constant current and constant voltage, with a cut-off current of 0.05C, and then discharged to 3.0V at 0.5C constant current. After 400 cycles of charge and discharge, the capacity retention rate at the 400th week is calculated. The calculation formula is as follows:
[0109] 400th cycle capacity retention rate (%) = (400th cycle discharge capacity / first cycle discharge capacity) × 100%,
[0110] Thickness growth rate at the 400th cycle = (thickness at full charge at the 400th cycle / thickness at full charge at the first cycle) × 100%.
[0111] (2) High temperature cycle performance test:
[0112] In a 45°C environment, the divided battery is charged to 4.55V at 0.7C constant current and constant voltage, with a cut-off current of 0.05C, and then discharged to 3.0V at 0.5C constant current. After 300 cycles of charge and discharge, the capacity retention rate at the 300th week is calculated. The calculation formula is as follows:
[0113] 300th cycle capacity retention rate (%) = (300th cycle discharge capacity / first cycle discharge capacity) × 100%,
[0114] Thickness growth rate at the 300th cycle = (thickness at full charge at the 300th cycle / thickness at full charge at the first cycle) × 100%.
[0115] (3) 85℃ 24h high temperature storage test:
[0116] The battery was placed at room temperature and charged and discharged once at 0.5C (3.0V-4.55V), and the discharge capacity C0 of the battery before storage was recorded. Then the battery was charged to 4.55V at constant current and constant voltage (100% SOC). The thickness d1 of the battery before high-temperature storage was tested using a PPG battery thickness gauge (600g). The battery was placed in an 85℃ constant temperature box and stored for 24h. After the storage was completed, the battery was taken out and the thermal thickness d2 of the battery after storage was tested. The thickness expansion rate of the battery after 85℃ storage for 24h was calculated. After the battery was cooled at room temperature for 24h, the battery was again discharged to 3.0V at 0.5C at constant current and then charged to 4.55V at 0.5C at constant current and constant voltage. The discharge capacity C1 and charge capacity C2 of the battery after storage were recorded. The capacity remaining rate and recovery rate of the battery after 85℃ storage for 24h were calculated as follows:
[0117] Thickness expansion ratio after storage at 85℃ for 24h = (d2-d1) / d1*100%;
[0118] After storage at 85℃ for 24h, the capacity remaining rate = C1 / C0*100%;
[0119] After storage at 85°C for 24 hours, the capacity recovery rate = C2 / C0*100%.
[0120] (4) Thermal shock performance:
[0121] Under 25℃ ambient conditions, discharge to 3.0V with a given current of 0.2C; leave for 5 minutes; charge to 4.55V with a charging current of 0.2C. When the cell voltage reaches 4.55V, change to 4.55V constant voltage charging until the charging current ≤ the cut-off current of 0.05C; after leaving for 1h, put the cell into an oven, increase the oven temperature to 135±2℃ at a rate of 5±2℃ / min, and keep it for 60 minutes before stopping. The judgment standard is that the cell does not catch fire or explode.
[0122] The results of the above performance tests are shown in Table 2.
[0123] Table 2 Lithium-ion battery and electrolyte performance test results
[0124]
[0125]
[0126] According to the data of the above embodiments and comparative examples, it can be seen that the thickness growth and cycle decay of the silicon negative electrode system during the cycle process are relatively fast, and the battery with a low liquid retention coefficient has a problem of water diving in the late stage of long cycle. The present invention introduces DFEC into the electrolyte system. DFEC has an efficient film-forming effect. It can preferentially form a film on the negative electrode during the formation process to form a SEI with a high LiF content, increase the ratio of LiF / Li2O in SEI and the ionic conductivity of SEI, and improve the charge and discharge performance. At the same time, the electrolyte suppresses the growth of the battery thickness during the cycle process, and suppresses the problem of water diving in the late stage of long cycle, avoiding safety hazards.
[0127] In addition, binary and ternary nitriles will also have a significant impact on the cycle process of the silicon system. They help to inhibit the dissolution of positive electrode metal ions under high voltage. By controlling the content of nitrile solvents in the electrolyte, the cycle performance of silicon negative electrode lithium-ion batteries can be effectively improved.
[0128] The lithium-ion battery of the embodiment of the present invention satisfies the following relationship: 8≤8*(α*β / 2+σ 2 )+30*ln(σ*u / 5+γ 2 / 25)+10 / min(σ*u*γ*v, σu / v, 100*w*α / β)≤130, wherein α, β, γ, and w are the mass percentages of FEC, DFEC, ADN, and HTCN in the electrolyte, σg / Ah is the battery's liquid retention coefficient, uμm is the median particle size of the silicon material, and v is the mass percentage of the silicon material in the active material. The lithium-ion battery of the present invention can not only meet the needs of long cycles, but also solve the safety risks caused by the drying up of the electrolyte in the late cycle.
[0129] The above content describes the embodiments of the present invention in detail, but the present invention is not limited to the above embodiments. Various changes can be made within the knowledge of ordinary technicians in the relevant technical field without departing from the purpose of the present invention. In addition, the embodiments of the present invention and the features in the embodiments can be combined with each other without conflict.
Claims
1. A lithium ion battery, characterized in that: include: Electrolyte; the electrolyte comprises a lithium salt, a solvent and an additive, wherein the additive comprises fluoroethylene carbonate, difluoroethylene carbonate, adiponitrile and 1,3,6-hexanetrinitrile; Positive electrode; A negative electrode plate; the active material of the negative electrode plate comprises silicon material and graphite; and, Isolation film; The lithium ion battery satisfies 8≤8*(α*β / 2+σ 2 )+30*ln(σ*u / 5+γ 2 / 25)+10 / min(σ*u*γ*v, σu / v, 100*w*α / β)≤130, wherein α is the mass percentage of the fluoroethylene carbonate in the electrolyte, β is the mass percentage of the difluoroethylene carbonate in the electrolyte, γ is the mass percentage of the adiponitrile in the electrolyte, w is the mass percentage of the 1,3,6-hexanetrinitrile in the electrolyte, σg / Ah is the liquid retention coefficient of the lithium ion battery, uμm is the median particle size of the silicon material, and v is the mass percentage of the silicon material in the active substance.
2. The lithium-ion battery according to claim 1, characterized in that The mass percentage of the fluoroethylene carbonate in the electrolyte is 1% to 20%; and / or the mass percentage of the difluoroethylene carbonate in the electrolyte is 0.4% to 10%; and / or the mass percentage of the adiponitrile in the electrolyte is 0.3% to 1.5%; and / or the mass percentage of the 1,3,6-hexanetrinitrile in the electrolyte is 0.3% to 3%.
3. The lithium-ion battery according to claim 1, characterized in that The mass percentage of the lithium salt in the electrolyte is 8% to 25%.
4. The lithium-ion battery according to claim 1, characterized in that: The solvent includes at least one of a non-fluorinated carbonate solvent, a carboxylate solvent, an ether solvent, and a C2-C5 nitrile solvent.
5. The lithium-ion battery according to claim 1, characterized in that: The positive electrode sheet comprises an aluminum foil current collector and a positive electrode membrane; wherein the positive electrode membrane comprises a positive electrode active material, lithium cobalt oxide.
6. The lithium-ion battery according to claim 1, characterized in that The silicon material is selected from at least one of silicon, silicon oxide, silicon monoxide and silicon carbide.
7. The lithium-ion battery according to claim 1, characterized in that: The weight proportion of the silicon material in the active material is 3% to 20%.
8. The lithium-ion battery according to claim 1, characterized in that The median particle size of the silicon material is 2.3-7 μm.
9. The lithium-ion battery according to claim 1, characterized in that: The liquid retention coefficient of the lithium ion battery is 1.0 to 1.5 g / Ah.
10. An electronic device, characterized in that: A lithium ion battery comprising the lithium ion battery according to any one of claims 1 to 9.
Citation Information
Patent Citations
Lithium ion battery electrolyte and lithium ion battery comprising same
CN108832180A
Lithium ion battery
CN114122494A
High-voltage lithium ion battery
CN116454381A
Battery, electrolyte layer, battery pack, electronic apparatus, electric vehicle, power storage device, and electric power system
US20160043429A1
Battery
WO2024169403A1
Cited By
Battery, battery pack and electric device
WO2026194904A1